Request strategies used by Malaysian ESL learners of four proficiency levels - Taw, Ly Wen (2014)
Pragmatic competence is defined as the ability to convey communicative actions in sociocultural contexts. Production of appropriate speech acts in a particular context is one of the important aspects of pragmatic competence. Making requests forms a large part of communicative events, and they thus play a significant role in communication. This study investigates the request strategies used by Malaysian ESL learners of four proficiency levels: elementary, lower intermediate, upper intermediate and advanced. The proficiency levels are obtained through benchmark standard as set by the Malaysian English University Test (MUET). The requests were discussed in terms of strategy types, and they are linked to their directness levels as well as internal and external modifications. The principal investigative tool was Oral Discourse Completion Task (ODCT), which is also called closed role play. It elicited the requests produced by 120 participants through six controlled situations which reflect common oral encounters. The Oral Discourse Completion Tasks were audio-recorded, transcribed and analysed using the request coding scheme developed by Blum-Kulka and Olshtain (1989) in Cross-Cultural Study of Speech Act Realisation Patterns (CCSARP).The findings revealed that pragmatic development moves from direct to conventionally indirect strategies in accordance to the learners‘ proficiency levels. Specifically, the elementary and lower intermediate proficiency learners displayed overuse of direct request strategy while the more proficient learners applied more conventionally indirect strategies in their requests. In addition, it can be concluded that Malaysian ESL learners overused external modifications and underused internal modifications. It suggests that Malaysian ESL learners have not acquired sufficient linguistic forms to mitigate their request utterances. This study contributes to the knowledge of how requests are made by Malaysian ESL learners in the university setting and request making is co-related with pragmatic competence of ESL learners. Overall, they showed a pattern of pragmatic development which reflects language proficiency levels situated in request making.